Role of Neighborhood Design in Reducing Impacts of Development and Climate Change, West Sherwood, OR - Tchintcharauli-Harrison, Michael B.; Santelmann, Mary V.; Greydanus, Hattie; Shehab, Omar; Wright, Maria (Frontiers in Water, 2022)
We used the EPA SWMM-5.1 model to evaluate the relative impact of neighborhood design and constructed Low Impact Development (LID) features on infiltration, evaporation, and runoff for three future scenarios. In the Current Course (CC) future, current regulations and policies remain in place under lower rates of climate change and population growth. In the Stressed Resources (SR) future, rapid rates of population growth and climate change stress water systems, and conventional development patterns and management actions fail to keep pace with a changing environment. In the Integrated Water (IW) future, with the same rapid rates of climate change and population growth as the SR future, informed water management anticipates and adapts to expected changes. The IW scenario retains public open space, extensive use of constructed LID features, and has the lowest proportion of impervious surface. We compared the scenarios using SWMM-5.1 for a set of NRCS Type 1a design storms with precipitation input at 6-minute time steps as well as a set of 10-year continuous runs. The design with the highest proportion of impervious surface produced runoff of up to 45-50% of precipitation for all variations of the 25-year storm, compared to 34-44% and 23-39% for the CC and IW futures, respectively. Evaporation accounted for only 2-3% of precipitation in the 25-year design storm simulations for any scenario. Results of continuous 10-year simulations were similar to the results of design storms. The proportion of precipitation that became runoff was highest in the SR future, intermediate in the CC, and lowest in the IW future. Evaporation accounted for 6%, 11%, and 14% of precipitation in the SR, CC and IW futures with LID, respectively. Infiltration was higher in scenarios with LID than for the same scenario without LID, and varied with the extent of LID employed, accounting for 59%, 71%, and 74% of precipitation in the SR, CC, and IW scenarios with LID. In addition to differences in performance for stormwater management, the IW and SR future designs both provide more housing than the CC, and the IW future has the lowest cost of development per dwelling unit.